Clinical, somatosensory and psychosocial characterization of patients with painful temporomandibular joint clicking: a cross-sectional study - Poluha, Rodrigo Lorenzi (2021)
Characterize patients with painful temporomandibular joint (TMJ) clicking can help to understand the arthralgia mechanisms in cases of TMJ clicking and to formulate a better clinical approach. The presented study aimed to characterize patients with painful TMJ clicking. Ninety individuals, equally divided into three groups, composed the sample: patients with painful TMJ clicking (n=30); patients with painless TMJ clicking (n=30); and, control group (n=30). Clinical data included: oral behaviors (OBs) (unilateral chewing; chewing gum; nail biting; bite foreign objects; lean with your hand on the jaw; sleep in a position that puts pressure on the jaw); sleep bruxism (SB); awake bruxism (AB); and, malocclusion. Somatosensory data included: mechanical pain threshold (MPT), wind-up ratio (WUR), pressure pain threshold (PPT), and the conditioned pain modulation (CPM) paradigm. Psychosocial data were formulated on the basis of some questionnaires: Pittsburgh Sleep Quality Index (PSQI); Pain Vigilance and Awareness Questionnaire (PVAQ); Pain Catastrophizing Scale (PCS); Tampa Scale for Kinesiophobia for Temporomandibular Disorders (TSK/TMD); Perceived Stress Scale (PSS); and, The State-Trait Anxiety Inventory (STAI). A 5% significance level was used for all statistical tests. Patients with painful TMJ clicking showed a significant association with specific OBs (lean with your hand on the jaw; sleep in a position that puts pressure on the jaw; use chewing gum; and, nail biting); presence of AB; higher values of MPT and WUR; lower PPT; less efficient CPM; and, higher scores of PSQI, PVAQ, PCS, and TSK/TMD when compared to the other groups (p<0.05). Patients with painless TMJ clicking showed a significant association with the OBs of chewing gum and nail biting; presence of AB; lower PPT; and, higher scores of PVAQ and TKS/TMD only when compared to the control group (p<0.05). No significant difference among groups was found for other OBs (unilateral chewing and bite foreign objects), BS, malocclusion, PSS, and STAI data. It can be concluded that patients with painful TMJ clicking were characterized by a significant association with specific harmful OBs, AB, a somatosensory gain of function (more sensitive) to mechanical pain tests and impaired CPM in the TMJ area, poor sleep quality along with higher levels of hypervigilance, pain catastrophizing, and kinesiophobia.